Utilizing the effect of nitrogen to implementation of light- oil air injection in Malaysian Oil Fields - Mohiuddin , Zeeshan (2007)
Air injection has been used as one of the enhanced oil recovery (EOR) techniques especially to extract the heavy oil. Nevertheless, a number of applications of in-situ combustion (ISC) for light oil reservoirs have been also reported successful. In light oil reservoirs, the thermal method of EOR is known as light oil air injection (LOAI). This paper discusses the research work carried out to find the potentials of LOAI in Malaysian light oil reservoirs. Screening criteria has been developed from which Dulang E12-14 reservoirs were short listed for further study. In research study, combustion was assumed to occur in low temperature oxidation (LTO) to eliminate the complexities of combustion process. In simulation studies, effect of nitrogen was utilized in place of air, as nitrogen has various common properties with air due to the higher percentage in it. By this assumption, the early potentials of LOAI can be identified without performing experimental studies. This method could provide an easy alternative to assess the potential application of the LOAI technique for depleting Malaysian light oil reservoirs. Experimental studies may need to be carried out if simulation results show the significant amount of incremental oil.